"I think the middle class is disappearing": Crisis perceptions and consumption patterns in Spain. (July 2017) - Alonso, Luis Enrique; Fernández Rodríguez, Carlos J.; Ibáñez Rojo, Rafael
Abstract: The aim of this article is to explore social discourses in Spain on the economic crisis under the scenario of austerity policies and cutbacks. The goal is to explore whether social perceptions have changed throughout the crisis that evolved from the collapse of the housing market bubble to a public deficit and debt problem, leading to record rates of unemployment and a dramatic decline in living standards. The long crisis has left an imprint on Spanish society and it is worthwhile exploring how Spanish citizens reflect upon the crisis. To do so, 18 focus groups were organized in two rounds (2010 and 2014) and the results of those group conversations are discussed and compared here. The analysis shows that the participants elaborated not only on reflections about the crisis and on how it has lowered their consumption levels, but also on their further views about the social structure and change. The notorious pessimism of Spaniards about their future, regardless of their class position, is highlighted in the results. A more critical narrative about the crisis seemed to emerge in 2014, leaving behind the guilt‐laden "living beyond our means" discourses that dominated in 2010.